Applicants reaction towards the personnel selection methods in Pakistan - Qandeel Hassan (Taylor & Francis Group, 2020)
The purpose of this study is to investigate applicants’ reactions towards different personnel selection methods used in Pakistan. A sample of 149 undergraduates, graduates, and working adults rated their perceptions of the favorability and fairness of these personnel selection methods, namely: resumes, job knowledge tests, biographical information, interviews, personal references, work-sample tests, personality tests, written ability tests, personal contacts, and situational judgment tests. Our first research objective is to provide details about applicant reactions, detailed system of the same and methods on a range based on working adults, graduates, and undergraduates. The second major objective is to identify the interaction effects of favorability and system fairness based upon applicant reactions. Descriptive data analysis was performed using IBM SPSS and the data was collected from Lahore, Islamabad, and Jhelum. The results demonstrated that 112 applicants reported the most favorable rating reaction towards the interview personnel selection method, with the effectiveness of identifying qualified people for the job, while 101 applicants reported a favorable rating reaction towards job knowledge tests, noting the fairness of this procedure. In addition, implications for the current assessment of selection practices from the applicants’ viewpoints, the strengths and limitations of the study, and directions for future research are all discussed. The practices of different predictor methods are considered in the conclusion.